Partisipasi Anggota Kelompok Tani Kinaskas di Kelurahan Kakaskasen Tiga - Mamuaja, Livita Dana; Kapantow, Gene Henfried Meyer; Lumingkewas, Jelly Ribka Danaly (Sam Ratulangi University, 2023)
The purpose of this study was to determine the participation of farmer group members in Kakaskasen III Village, Tomohon Utara Sub-district, Tomohon City. This research was conducted for three months from July 2022 to September 2022. Starting from preparation until the preparation of the research report. The place of research was Kinaskas Farmers Group in Kakaskasen III Village, North Tomohon District, Tomohon City. The method of data collection carried out in the research is the method of observation and direct interviews to obtain facts and information from the sample using questionnaire tools. The types of data taken in the study are primary data and secondary data. Primary data is data taken in the field directly from vegetable farmers in Kakaskasen Village who are the research sample, using a list of questions that have been prepared. Secondary data were obtained from government agencies or institutions related to the research such as the Agricultural Extension Center (BPP), village offices and sub-district offices and internet references. Participation of farmer group members, using direct observation method, namely data collection method by observing directly in the field. The analysis was done descriptively. The results showed that kinaskas farmer group members were classified as very active at the implementation stage and active in decision-making activities but less active in the evaluation section. There needs to be an effort from the group management to increase the involvement of group members in evaluation activities because this activity is very important in improving group performance.